1999
DOI: 10.1002/(sici)1097-0142(19990825)87:4<224::aid-cncr10>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Bcl‐2 expression on fine‐needle aspirates from primary breast carcinoma

Abstract: Bcl-2 expression, evaluated by immunocytochemistry on FNAs from primary breast carcinoma, correlates with favorable prognostic features such as ER and PgR expression, p53 negativity, a low Ki-67 index, and high tumor differentiation. These results are in agreement with those found on histologic samples. As FNA biopsy is used increasingly as a primary tool in the diagnosis of breast carcinoma, Bcl-2 evaluation by immunocytochemistry on FNA may provide, in addition to other biologic variables, useful information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
4
13
0
2
Order By: Relevance
“…In our study, we found no association between the invasive lesions of EMPD and p53 expression. In addtion, a previous study revealed that Bcl-2 expression was only seen at a low incidence in EMPD [29] compared with breast carcinomas [30,31]. Also in the present…”
supporting
confidence: 73%
“…In our study, we found no association between the invasive lesions of EMPD and p53 expression. In addtion, a previous study revealed that Bcl-2 expression was only seen at a low incidence in EMPD [29] compared with breast carcinomas [30,31]. Also in the present…”
supporting
confidence: 73%
“…Overexpression has been shown to prevent or delay apoptosis induced by g-irradiation, growth factor deprivation, glucocorticoids, and various chemotherapeutic agents. Bcl-2 has been detected in 46±76% [46±48] of breast carcinomas, and its presence has been associated with other favorable prognostic factors such as ER and PR expression, a low Ki-67 index, p53 and Her-2/neu negativity [28,49], and low histologic tumor grade [48]. It is present in normal breast epithelium and may be an estrogen-related protein that is involved in the glandular cell renewal system of the breast [49].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the expression of BCL2, MDM2, MDM4, PTEN and USP7 has been associated with the 'luminal-like' phenotype of breast cancer cells (BCC) and/or tumours (Bozzetti et al 1999, Kappes et al 2001, Phelps et al 2003, Garcia et al 2004, Lacroix et al 2004, Charafe-Jauffret et al 2006.…”
Section: Alterations Of P53 Modulator And/or Target Proteinsmentioning
confidence: 99%